Dynamic optical code division multiple access communication system analysis and performance enhancement by signal clipping - Hamarsheh, Mohammad M. Naji; Abdullah, Mohamad Khazani; Mahdi, Mohd Adzir; Khatun, Sabira; Shalaby, Hossam M. H. (IEEE (IEEE Xplore), 2005)
Dynamic optical code division multiple access (DOCDMA) communication system is proposed. In a DOCDMA system, the central wavelength of electrically controlled tunable optical filter (TOF) at the transmitter is dynamically varied during the bit period according to a functional code. An enhancement of the system is also proposed by clipping the signal at the decoder of each receiver. The system is modeled and analyzed with and without signal clipping taking into account the multiple access interference, thermal noise, and phase induced intensity noise. The performance of the enhanced system is compared with that of a DOCDMA system without signal clipping, fast frequency hopping, and with a spectral amplitude coding system that uses either a Hadamard code, a modified quadratic congruence code, or modified frequency hopping code. The results show that the proposed system improve the bit error rate performance. Signal clipping method reduces the multiple access interference and improve the bit error rate performance of the system.